The West Midlands ActiVe lifestyle and healthy Eating in School children (WAVES) study: a cluster randomised controlled trial testing the clinical effectiveness and cost-effectiveness of a multifaceted obesity prevention intervention programme targeted at children aged 6-7 years. - Adab, Peymane (Health Technol Assess, 2018)
BACKGROUND: Systematic reviews suggest that school-based interventions can be effective in preventing childhood obesity, but better-designed trials are needed that consider costs, process, equity, potential harms and longer-term outcomes. OBJECTIVE: To assess the clinical effectiveness and cost-effectiveness of the WAVES (West Midlands ActiVe lifestyle and healthy Eating in School children) study intervention, compared with usual practice, in preventing obesity among primary school children. DESIGN: A cluster randomised controlled trial, split across two groups, which were randomised using a blocked balancing algorithm. Schools/participants could not be blinded to trial arm. Measurement staff were blind to allocation arm as far as possible. SETTING: Primary schools, West Midlands, UK. PARTICIPANTS: Schools within a 35-mile radius of the study centre and all year 1 pupils (aged 5-6 years) were eligible. Schools with a higher proportion of pupils from minority ethnic populations were oversampled to enable subgroup analyses. INTERVENTIONS: The 12-month intervention encouraged healthy eating/physical activity (PA) by (1) helping teachers to provide 30 minutes of additional daily PA, (2) promoting 'Villa Vitality' (interactive healthy lifestyles learning, in an inspirational setting), (3) running school-based healthy cooking skills/education workshops for parents and children and (4) highlighting information to families with regard to local PA opportunities. MAIN OUTCOME MEASURES: The primary outcomes were the difference in body mass index z-scores (BMI-zs) between arms (adjusted for baseline body mass index) at 3 and 18 months post intervention (clinical outcome), and cost per quality-adjusted life-year (QALY) (cost-effectiveness outcome). The secondary outcomes were further anthropometric, dietary, PA and psychological measurements, and the difference in BMI-z between arms at 27 months post intervention in a subset of schools. RESULTS: Two groups of schools were randomised: 27 in 2011 (n = 650 pupils) [group 1 (G1)] and another 27 in 2012 (n = 817 pupils) [group 2 (G2)]. Primary outcome data were available at first follow-up (n = 1249 pupils) and second follow-up (n = 1145 pupils) from 53 schools. The mean difference (MD) in BMI-z between the control and intervention arms was -0.075 [95% confidence interval (CI) -0.183 to 0.033] and -0.027 (95% CI -0.137 to 0.083) at 3 and 18 months post intervention, respectively. The main analyses showed no evidence of between-arm differences for any secondary outcomes. Third follow-up included data on 467 pupils from 27 G1 schools, and showed a statistically significant difference in BMI-z (MD -0.20, 95% CI -0.40 to -0.01). The mean cost of the intervention was £266.35 per consented child (£155.53 per child receiving the intervention). The incremental cost-effectiveness ratio associated with the base case was £46,083 per QALY (best case £26,804 per QALY), suggesting that the intervention was not cost-effective. LIMITATIONS: The presence of baseline primary outcome imbalance between the arms, and interschool variation in fidelity of intervention delivery. CONCLUSIONS: The primary analyses show no evidence of clinical effectiveness or cost-effectiveness of the WAVES study intervention. A post hoc analysis, driven by findings at third follow-up, suggests a possible intervention effect, which could have been attenuated by baseline imbalances. There was no evidence of an intervention effect on measures of diet or PA and no evidence of harm. FUTURE WORK: A realist evidence synthesis could provide insights into contextual factors and strategies for future interventions. School-based interventions need to be integrated within a wider societal framework and supported by upstream interventions. TRIAL REGISTRATION: Current Controlled Trials ISRCTN97000586. FUNDING: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full inHealth Technology Assessment; Vol. 22, No. 8. See the NIHR Journals Library website for further project information.